ETHNOBOTANICAL SURVEY OF CHITTERI HILLS OF EASTERN GHATS IN DHARMAPURI DISTRICT-TAMILNADU - D. ANANDHA KUMAR, G. PRABAKARAN,; M. MURALI, R. PUGALVENDHAN, (Journal of Medicinal Herbs and Ethnomedicine)
Flora and fauna diversities are two facts components of biodiversity which covers the variety and variability of species. A survey was conducted to study the rare plants of chitteri hills, Tamil Nadu, India. 96 Plants Belonging to 48 Family, 90 Genus and 96 species were Documented Plants totally were under thorough investigation. Of these monocots are represented by 7 species belonging to 7 genera and 4 families, while dicot contributed by 87 species belonging to 82 genera and 39 families, Ferns 2 families and 2 genera, Fungi 1 family and 1 Genera. Plant species were recorded and identified during the survey. The results show that the habitat of plants belongs to herbs, shrubs and tree species. But, we have observed only minimum tree species. Of these monocots are represented by 7 species belonging to 7 genera and 4 families, while dicots contributed by 87 species belonging to 82 genera and 39 families, Ferns 2 families and 2 genera, Fungi 1 family and 1 Genera. The study decipts that Chitteri Hills have different variety of plants distributed all over the mountain.